Tailoring Photocatalytic Activity of Sol-Gel-Derived Bismuth Oxide via Calcination Time Optimization for Methyl Orange Degradation - Yayuk Astuti; Agus Muslim; Adi Darmawan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Bismuth oxide (Bi2O3) is a yellow solid, has good electrical properties and a wide band gap energy (2-3.96 eV). Therefore, this material is commonly used as a photocatalyst. This study aims to synthesize bismuth oxide using the sol-gel method, determine its physicochemical characteristics and photocatalytic activity in the degradation of methyl orange dyes. Bi2O3 is synthesized from Bi(NO3)3.5H2O which is reacted with citric acid at 100 ° C for 20 hours. The formed gel is then dried and calcined at 600 °C for 1, 2, 3, 4 and 5 hours. The synthesis results in the form of pale-yellow powder with the same crystal system that is a mixture of α-Bi2O3 (monoclinic) and γ-Bi2O3 (BCC) and has almost the same morphology that is similar to coral and has a particle size of 1-8 μm. The results of photocatalytic activity tests showed that the constant rate of degradation reaction of methyl orange by bismuth oxide with calcination time of 1, 2, 3, 4, and 5 hours respectively was 2.76×10-5 s-1, 2.65×10-5 s-1, 2.53×10-5 s-1, 2.81×10-5 s-1 and 3.87×10-5 s-1. Bismuth oxide with a calcination time of 5 hours has the highest photocatalytic activity. Meanwhile, bismuth oxide with a calcination time of 5 hours has a band-gap of 2.86 eV and 2.64 eV. The stages of decomposition of bismuth oxide material with a calcination time of 5 hours consisted of 3 release stages namely H2O, CO2, CxHyOz respectively 12.20%, 5.33% 30.54%. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).